(9-3g)-(3+12g)=

Simple and best practice solution for (9-3g)-(3+12g)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (9-3g)-(3+12g)= equation:


Simplifying
(9 + -3g) + -1(3 + 12g) = 0

Remove parenthesis around (9 + -3g)
9 + -3g + -1(3 + 12g) = 0
9 + -3g + (3 * -1 + 12g * -1) = 0
9 + -3g + (-3 + -12g) = 0

Reorder the terms:
9 + -3 + -3g + -12g = 0

Combine like terms: 9 + -3 = 6
6 + -3g + -12g = 0

Combine like terms: -3g + -12g = -15g
6 + -15g = 0

Solving
6 + -15g = 0

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + -15g = 0 + -6

Combine like terms: 6 + -6 = 0
0 + -15g = 0 + -6
-15g = 0 + -6

Combine like terms: 0 + -6 = -6
-15g = -6

Divide each side by '-15'.
g = 0.4

Simplifying
g = 0.4

See similar equations:

| log(x-1)-log(x+1)-log(8)=-2 | | 2x-7y+z=-5 | | x^3+4x^2+60x-17=0 | | log(x-1)-2*log(x+1)-log(8)=-2 | | x+2x+2=2 | | -3=57+(n+1)-4 | | -3m(m-10)=0 | | 5x-7=3(x+3) | | -3x=40000 | | 5x-11=2(x+14) | | 40-8x=32 | | -3a-16b-38a+24b= | | 5x-8/2=2x | | 2*6x-52=9x-196 | | x=42-10+4 | | s*4-39=9 | | 60x=0 | | 1*6x-52=9x-196 | | 10*6x-52=9x-196 | | 4x-34=14 | | x-x/2-x/6=40000 | | sinx=sin(5^/9 | | sinx=sin(5pie/9 | | X*x+1=702 | | X^3+5x^2+6x+1=0 | | Sinx=sin(3pi/5 | | sin=sin(5pi/9) | | ln(15x-20)-ln(5)=3 | | Cosx=cos-11pi/9 | | x^2+mx-2m=0 | | 57x-10y=m | | Tan64=x/15 |

Equations solver categories